Improving Student Learning Outcomes in Aqidah Akhlak Learning at MTs S NW Tembeng Putik Through Active Learning Models - Kusumawati; Lalu Chairul Anam (Indonesian Journal of Education and Social Humanities, 2025)
This study aims to improve the activeness and learning outcomes of class II students of MI Yakti Ngadirejo in the subject of Akidah Akhlak by using the application of the mastery learning model. This study is a classroom action research consisting of three cycles. The subjects used in this study were 15 class II students of MI Yakti Ngadirejo. Each cycle consists of four stages, namely the planning, action, observation, and reflection stages. The instruments used to collect data were observation sheets, field notes, and daily test assessment sheets (evaluation). The results of the study showed an increase in student activeness in learning and student learning outcomes in the form of an increase in daily test scores from students who were used as subjects in this study. This increase occurred after students were guided in learning with the mastery learning model approach (complete learning). This is also supported by the results before and after the action. Thus, it can be concluded that learning with the mastery learning model approach is able to improve the activeness and learning outcomes of class II students of MI Yakti Ngadirejo in the subject of Akidah Akhlak.